Optimised process for fabricating tapered long period gratings - Mullaney, Kevin; Staines, Stephen E.; James, Stephen W.; Tatam, Ralph P. (SPIE - International Society for Optics and Photonics, 2017)
The process of fabricating tapered long period gratings (TLPGs) using a CO2 laser is described. TLPGs with a period spacing of 378 μm, were fabricated by optimization of the taper waist diameter and careful control of the duty-cycle and its uniformity along the length of the grating. The 6-period TLPGs exhibited a pass-band insertion loss of 0.6 dB, resonance band extinction values of 3 dB and had a physical length of 2.27 mm.